Measurement issues in longitudinal studies of mental health problems in children with neurodevelopmental disorders - Magnus Ivarsson; Henrik Danielsson; Christine Imms (BMC Psychology)
Abstract Purpose To develop and test an approach for assessing the risk of bias in four measurement-related domains key to the study of mental health problem trajectories in children with neurodevelopmental disorders (NDD): (1) conceptual overlap between mental health problems and NDD diagnostic criteria, (2) over-reliance on a single informant, (3) unwarranted omission of the child’s perspective, and (4) the use of instruments not designed for or adapted to the population. Methods Building upon a previous systematic review, this study established supplementary criteria for assessing the risk of bias domains. Following this, the criteria were applied to measures used in 49 longitudinal studies of mental health problems in children with NDD. Results The general risk of bias across domains was rated as high in 57.1% of the 49 included studies. The highest risk of bias was seen in domain four (rated as high in 87.8% of studies) and the lowest in domain three (24.5%). Conclusions The risk of bias items enhance our understanding of the quality of the evidence about mental health problem trajectories in children with NDD. The methodological quality of future research can be increased by selecting conceptually clear scales developed for the population - preferably in the form of cognitively accessible self-report scales - and adopting a multi-informant approach.